Endoscopic submucosal dissection for gastric adenomyoma: A rare entity of 15 cases among 571 patients with gastric submucosal eminence lesions. Issue 9 (March 2017) - Wang, Sinan; Cao, Hailong; Zhang, Yujie; Xu, Mengque; Chen, Xue; Piao, Meiyu; Wang, Bangmao
Abstract : Abstract: Gastric adenomyoma (GA) is a kind of rare gastric submucosal eminence lesions. As the malignant transformation cannot be ruled out, surgery and laparoscopic resection are usually considered. The aim of this study is to evaluate the therapeutic effect and safety of endoscopic submucosal dissection (ESD) for GA. All of the patients with gastric submucosal eminence lesions who underwent ESD from June 2008 to June 2015 in General Hospital, Tianjin Medical University, China, were identified, and patients with GA, which was confirmed by pathological evaluation, were enrolled for further analysis. Among the 571 patients who received ESD, 15 cases with uncertain diagnosis before the procedure were finally confirmed as GA. The mean age of these 15 patients was 46.93 ± 15.56 years (range: 18–73). Most of the lesions were located in antrum (12/15 patients), with 2 in the body of stomach and 1 in cardia, respectively. The mean size of the lesions was 1.47 ± 0.67 cm (range: 0.4–3.0). According to the endoscopic ultrasonography, the lesions of 14 patients originated from submucosa and 1 originated from superficial muscularis, totally with mixed echoes changes. En bloc complete resection was achieved in all of the lesions. No perforation, intraoperative bleeding, delayed bleeding, and mortalities occurred. No recurrence or metastasis was found during 1 to 67 months. ESD appears to be a feasible, safe, and effective treatment for GA with clinical presentation of gastric submucosal eminence lesions.